Cross-Cultural Adaptation, Validation, and Reliability of the Indonesian Version of Kidney Disease and Quality of Life (The KDQOL-SF™ v1.3) Instrument - Syamsiah, Nita; Said, Faridah Binti Mohd; Hassan, Datin Hafizah Che; Nurjanah, Uun (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: The Kidney Disease and Quality of Life Short Form (KDQOL-SF™ v1.3) was specifically developed to assess quality of life in individuals with kidney disease, including those not yet requiring dialysis. With the increasing burden of chronic kidney disease (CKD) in Indonesia, there is a need for culturally adapted and psychometrically sound instruments. Objective: This study aimed to adapt, validate, and evaluate the reliability of the Indonesian version of the KDQOL-SF™ v1.3 among hemodialysis patients. Methods: The KDQOL-SF™ v1.3 was adapted for cultural use by following international guidelines, including forward and backward translation, expert review, and interviews with patients. A total of 190 hemodialysis patients took part in the study. Construct validity was tested using factor analysis, and convergent validity was checked by comparing it with the EQ-5D-5L quality of life scale. Differences in scores between early-stage CKD patients and those on hemodialysis were used to test known-groups validity. Reliability was measured through internal consistency (Cronbach’s alpha) and a two-week test–retest method. Results: Of the 225 patients invited, 190 (84.4%) completed the survey. The content validity index (CVI) ranged from 0.73 to 1.00 across items. Exploratory factor analysis revealed factor loadings between 0.501 and 0.872, supporting construct validity. Significant correlations between the KDQOL-SF™ v1.3 domain scores and EQ-5D-5L measures confirmed convergent validity. Known-groups validity was demonstrated by significantly lower scores in physical function, role-physical, mental health, general health, pain, and fatigue domains among hemodialysis patients compared to those with earlier-stage CKD (p < 0.05). Cronbach’s alpha values ranged from 0.710 to 0.883 across domains, indicating good internal consistency, while test-retest reliability coefficients ranged from 0.702 to 0.852. Conclusion: The Indonesian version of the KDQOL-SF™ v1.3 is a valid and reliable tool to measure quality of life in hemodialysis patients. It can be used in both clinical practice and research to support patient-centered care and track outcomes. Future research should look at how well the tool detects changes in health and whether it works for patients with other stages of CKD